Alpha power oscillation in the frontal cortex under Bromazepam and Modafinil effects - Danielle Aprigio; Washington Adolfo; Juliana Bittencourt; Mariana Gongora; Silmar Teixeira; Luis Fernando Basile; Henning Budde; Mauricio Cagy; Pedro Ribeiro; Bruna Velasques (Arquivos de Neuro-Psiquiatria)
ABSTRACTObjective Our aim was to investigate and compare the neuromodulatory effects of bromazepam (6 mg) and modafinil (200 mg) during a sensorimotor task analyzing the changes produced in the absolute alpha power.Method The sample was composed of 15 healthy individuals exposed to three experimental conditions: placebo, modafinil and bromazepam. EEG data were recorded before, during and after the execution of the task. A three-way ANOVA was applied, in order to compare the absolute alpha power among the factors: Group (control, bromazepam and modafinil) Condition (Pre and Post-drug ingestion) and Moment (pre and post-stimulus).Results Interaction was found between the group and condition factors for Fp1, F4 and F3. We observed a main effect of moment and condition for the Fp2, F8 and Fz electrodes.Conclusion We concluded that drugs may interfere in sensorimotor processes, such as in the performance of tasks carried out in an unpredictable scenario.